Attentional dynamics during free picture viewing: Evidence from oculomotor behavior and electrocortical activity - Fischer, Thomas; Graupner, Sven-Thomas; Velichkovsky, Boris M.; Pannasch, Sebastian (Frontiers in Systems Neuroscience, 2013)
Most empirical evidence on attentional control is based on brief presentations of rather abstract stimuli. Results revealed indications for a dynamic interplay between bottom-up and top-down attentional mechanisms. Here we used a more naturalistic task to examine temporal signatures of attentional mechanisms on fine and coarse time scales. Subjects had to inspect digitized copies of sixty paintings, each shown for 40 seconds. We measured simultaneously oculomotor behavior and electrophysiological correlates of brain activity to compare early and late intervals (1) of inspection time of each picture (picture viewing) and (2) of the full experiment (time on task). For picture viewing, we found an increase in fixation duration and a decrease of saccadic amplitude while these parameters did not change with time on task. Furthermore, early in picture viewing we observed higher spatial and temporal similarity of gaze behavior. Analyzing electrical brain activity revealed for components of the eye fixation-related potential (EFRP; C1, N1 and P2) changes during picture viewing; no variation was obtained for the power in the frontal beta- and in the theta activity. Time on task analyses demonstrated no effects on the EFRP amplitudes but an increase of power in the frontal theta and beta band activity. Thus, behavioral and electrophysiological measures similarly show characteristic changes during picture viewing, indicating a shifting balance of its underlying (bottom-up and top-down) attentional mechanisms. Time on task also modulated top-down attention but probably represent a different attentional mechanism.